The Women-only Passenger Carriage: Is It Helpful? - Prabowo, Hendro; Rebeca, Andreana; Salve, Henny R.; Fatimah, Firda F.; Chrisnatalia, Maria; Prabawati, Ira N.; Handayani, Nita S. (UI Scholars Hub, 2020)
In large metro areas such as Jakarta, Bogor, Tangerang, and Bekasi, the electric train (KRL) is a popular means of transportation because it runs quickly and on time despite being crowded. To help prevent the sexual harassment of female passengers, some KRL carriages are designated specifically for women. This study examines differences in female KRL passengers’ anxiety about sexual harassment in mixed carriages and women-only carriages on the Bogor–Jakarta route (n = 100) and Bekasi – Jakarta route (n = 110), using the Anxiety About Sexual Harassment Scale (Leitenberg & McNeil, 1990; Dacey, 2000). Significant differences in anxiety about sexual harassment were found among women who rode in women-only versus mixed carriages on the Bogor–Jakarta route but not on the Bekasi–Jakarta route. However, in general, participants who rode women-only carriages had higher anxiety than those who rode mixed carriages. This finding was confirmed by interviews with 35 female passengers (7 from the Bogor–Jakarta route, 28 from the Bekasi–Jakarta route). Some women expressed a preference for riding mixed cars because male passengers made room for them to enter or exit the cars and offered them seats. Meanwhile, some participants reported not choosing women-only carriages because the other passengers behaved aggressively.